The Article Review Penggunaan Aspirin sebagai Faktor Pemicu Sindrom Reye - Radwa, Ghaniyyah Atifah; Fatikha Rudia Ahda; Indri Setiawati; Khaula Karima; Ni Made Ayu Shinta Dewi; Arif Zuhan (Faculty of Medicine, Universitas Mataram, 2023)
Reye syndrome (RS) is a rare metabolic disorder which primarily affects children. The disease is generally characterized by acute encephalopathy and fatty degeneration of several parenchymes, especially the liver. Aspirin or acetylsalicylic acid is an over-the-counter drug as a solution to viral infection that would be the trigger for developing this syndrome. Reye syndrome is most commonly caused by viral pathogens like influenza A and B and varicella. Reye syndrome presents signs and symptoms of continued vomiting with or without dehydration, encephalopathy and, in 50% of patients, hepatomegaly. According to the clinical stage developed and modified by Hurwitz, the clinical stage of Reye syndrome is divided in 0-5, including the non-clinical stage (stage 0). The pathophysiological profile of Reye syndrome is unknown. However, it appears to be associated with mitochondrial dysfunction caused by the use of aspirin resulting in impaired fatty acid metabolism, reduced excretion, and impaired hepatic metabolism. A case-control study suggested a strong association between aspirin-taking behavior and the development of Reye's syndrome. A case-control study suggested a strong association between aspirin-taking behavior and the development of Reye's syndrome. This literature will present a discussion of the relationship of aspirin as a trigger for Reye syndrome based on the etiology, pathophysiology, and pharmacodynamics of aspirin.